Combinatorial Optimization and Applications 8th International Conference, COCOA 2014, Wailea, Maui, HI, USA, December 19-21, 2014, Proceedings - Zhang, Zhao; Wu, Lidong; Xu, Wen; Du, Ding-Zhu (Theoretical Computer Science and General Issues,, 2014)
This book constitutes the refereed proceedings of the 8th International Conference on Combinatorial Optimization and Applications, COCOA 2014, held on the island of Maui, Hawaii, USA, in December 2014. The 56 full papers included in the book were carefully reviewed and selected from 133 submissions. Topics covered include classic combinatorial optimization; geometric optimization; network optimization; optimization in graphs; applied optimization; CSoNet; and complexity, cryptography, and games.